Technical performance of basalt fiber reinforced polymer BFRP confined RC driven piles new construction methodology - Prakash Arul Jose, J; Rajesh Prasanna, P; Prakash, Fleming (International Journal of Engineering and Technology, 2018)
Pile foundations are often necessary to support large structures when the surface soil conditions are not strong enough to support the structure with shallow foundations. Pile foundation can be founded in dense sand layers at deeper, and also provide additional frictional support along their length to resist vertical loads. Load carrying capacity of Basalt FRP confined and unconfined piles were found out using the dynamic formulae and pile load test. Safe load carrying capacity of piles determined from piles load test was slightly higher than the dynamic formulae. The experimental result also shows that surface roughness of specimen is significantly changes the interface friction angle. The shear strength at the interface increases with the increase in surface roughness of the specimens.Â